Halogen Bonding from a Hard and Soft Acids and Bases Perspective: Investigation by Using Density Functional Theory Reactivity Indices. Issue 2 (21st November 2012) - Pinter, Balazs; Nagels, Nick; Herrebout, Wouter A.; De Proft, Frank
Abstract Halogen bonds between the trifluoromethyl halides CF3Cl, CF3Br and CF3I, and dimethyl ether, dimethyl sulfide, trimethylamine and trimethyl phosphine were investigated using Pearson's hard and soft acids and bases (HSAB) concept with conceptual DFT reactivity indices, the Ziegler–Rauk‐type energy‐decomposition analysis, the natural orbital for chemical valence (NOCV) framework and the non‐covalent interaction (NCI) index. It is found that the relative importance of electrostatic and orbital (charge transfer) interactions varies as a function of both the donor and acceptor molecules. Hard and soft interactions were distinguished and characterised by atomic charges, electrophilicity and local softness indices. Dual‐descriptor plots indicate an orbital σ hole on the halogen similar to the electrostatic σ hole manifested in the molecular electrostatic potential. The predicted high halogen‐bond‐acceptor affinity of N‐heterocyclic carbenes was evidenced in the highest complexation energy for the hitherto unknown CF3I⋅NHC complex. The dominant NOCV orbital represents an electron‐density deformation according to a n→σ*‐type interaction. The characteristic signal found in the reduced density gradient versus electron‐density diagram corresponds to the non‐covalent interaction between contact atoms in the NCI plots, which is the manifestation of halogen bonding within the NCI theory. The unexpected CX bond strengthening observed in several cases was rationalised within the molecular orbital framework.